MALE AND FEMALE LANGUAGE FEATURES IN A STAR IS BORN MOVIE - Rosita Setyadi; Rosyida Ekawati (Universitas 17 Agustus 1945 Surabaya, 2021)
Male and female often have their own language features that are also appear on the use of language in a movie. Lead male and female characters in A Star Is Born have their language features. This study is to discuss the language features in the movie and factors which underlie the occurrence of the language features. This is a qualitative study in which the data of this study are in the form of utterances produced by lead male and female characters in A Star Is Born movie. The data were collected by using a non-participant observation method and analyzed from the perspectives of Lakoff (1973) and Xia (2013) on language features, and Holmes (2013) on social factors. The result of the study shows that there are differences and similarities of lead male and female characters in using language. Both lead male and female characters use adjective feature to express their feeling and utilize swear word to show their emotion. Subsequently, in inviting each other, lead male character utilizes rising intonation, while lead female uses super polite form. Besides, in opening a show, the lead male character uses lexical hedges and fillers, while lead female applies super polite form. Nonetheless, the lead male character is inclined to use adverb and lexical hedges and filler in his utterance, while the lead female does not utilize those features. The occurrences of the language features in the lead characters are influenced by participants, setting, topic, and function.